PROSES MANAJEMEN PENDIDIKAN DI SMP NEGERI 9 KOTA SORONG - Dinda Irdayani Soulisa (SOSCIED, 2022)
This study aims to determine the education management process at SMP Negeri 9 Sorong City. This research is a descriptive qualitative research. The data collection used in this research is observation, interviews, and documentation. Sources of data in the form of primary data and secondary data. The data analysis stage in qualitative research generally starts from data collection, data reduction, and data presentation. The results of this study indicate that (1) The educational process of SMP Negeri 9 Sorong City, with the aim of the educational process at SMP Negeri 9, the education process will run effectively through an optimal and efficient learning process and learning experience. Because the development of student behavior as a learning goal that is focused on the existence of an optimal learning experience by paying attention to the function of education in the form of a. Planning (planning), b. Organizing (organizing), c. Actuanting (activities), d. Controlling (supervision). (2) SMP Negeri 9 Sorong City does not apply MOS, by handling the student orientation period which affects character building and introduction to the school environment, and only involves teachers in providing socialization; (3) SMP Negeri 9 Sorong City is still waiting for the technical technical assessment for the national assessment, West Papua Pos visited one of the leading schools in Sorong City, namely the State Junior High School (SMP) 9 Sorong City which once held the title as a reference school